2022
DOI: 10.1126/sciadv.abn2018
|View full text |Cite
|
Sign up to set email alerts
|

FCHO controls AP2’s initiating role in endocytosis through a PtdIns(4,5)P 2 -dependent switch

Abstract: Clathrin-mediated endocytosis (CME) is the main mechanism by which mammalian cells control their cell surface proteome. Proper operation of the pivotal CME cargo adaptor AP2 requires membrane-localized Fer/Cip4 homology domain-only proteins (FCHO). Here, live-cell enhanced total internal reflection fluorescence–structured illumination microscopy shows that FCHO marks sites of clathrin-coated pit (CCP) initiation, which mature into uniform-sized CCPs comprising a central patch of AP2 and clathrin corralled by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 102 publications
1
14
0
Order By: Relevance
“…Several additional clathrin adapter proteins have since been recognized as being recruited by PI(4,5)P 2 , including epsin [ 70 ] and AP180 [ 71 ]. In addition to being a simple membrane anchor, PI(4,5)P 2 also seems to play a pivotal role in the allosteric activation of AP-2 complexes on the membrane [ 72 , 73 ].…”
Section: Pm Transportmentioning
confidence: 99%
“…Several additional clathrin adapter proteins have since been recognized as being recruited by PI(4,5)P 2 , including epsin [ 70 ] and AP180 [ 71 ]. In addition to being a simple membrane anchor, PI(4,5)P 2 also seems to play a pivotal role in the allosteric activation of AP-2 complexes on the membrane [ 72 , 73 ].…”
Section: Pm Transportmentioning
confidence: 99%
“…Assuming independent binding sites for PtdIns(4,5)P2 and for cargo on AP2, the removal of the PtdIns(4,5)P2 binding effect results in an equilibrium-derived KD = 24.5 ± 1.6 nM and 75 ± 9 nM, for TGN38 and for CD4 respectively (Figure 2F, Table 1). The lower affinity for TGN38 peptide to its binding site on AP2 determined in solution by ITC (2 M) suggest lipid head groups also contribute to AP2 binding 25 . In support of this observation, AP2 has an overall weaker affinity to more densely packed PM model monolayers, which had larger initial pressure   = 35 ± 0.5 mN/m (overall affinity weakening from KD = 15 ± 3 nM to 64 ± 10 nM and from 29.5 ± 5 nM to 93 ± 10 nM, for a TGN-and a CD4-enriched PM monolayer respectively) as shown Figure 2G.…”
Section: Equilibrium Binding Analysis Of Ap2 To a Model Pm Shows Syne...mentioning
confidence: 99%
“…Correspondingly, the clathrin binding site in the 2-hinge, which is occluded in the close-state conformation, is presumed rendered accessible on membrane binding based on protein:protein interaction and basic CCV reconstitution assays 24 . Extrapolating from these 'static' molecular structures to in cell analysis of CME has proven insightful 25,26,27 , but these studies suffer from a lack of dynamic physical description and energetic analysis of the collective mechanisms and driving forces, which couple AP2 cargo assembly to membrane processes. Such in vitro approach may provide insights to why almost half of nascent CCPs fail to mature into cargo-loaded CCVs and are instead aborted, as determined by live-cell microscopy 8,16,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that recruitment of the AP2 adaptor complex to CME sites occurs shortly after CME site initiation 6,14 , a process that some studies suggest is facilitated by liquid condensate formation on the plasma membrane by endocytic pioneer proteins, including EPS15 and FCHO 6,13 . While DNM2 is well known for its crucial role in vesicle scission during the final step of CME, our genome-edited DNM2-TagGFP2 faithfully reflects its recruitment to CME sites in two phases, low-level recruitment during the assembly stage followed by a short burst of high-level recruitment during the late stage of CME 20,22,23 .…”
Section: Itsn1 Is Recruited During the Stabilization Stage Of Cme Sit...mentioning
confidence: 99%
“…Combining knowledge of the ultrastructural organization of endocytic proteins from super-resolution imaging 12 and evidence for liquid condensate formation, a two-phase CME protein network assembly model has recently been proposed 13 . This model suggests that subsequent to CME site initiation, proposed to involve the first liquid-liquid phase separation event, a second liquid-liquid phase separation event occurs involving Epsins and CALM, producing a protein network located at the center of the initial condensate, outcompeting EPS15 for binding to the cargo-bound AP2 complex 10,13,14 . However, the molecular mechanism underlying the formation of this second phase and how the two putative phases are connected remains to be determined.…”
Section: Introductionmentioning
confidence: 99%